2022
DOI: 10.1007/s12369-022-00884-z
|View full text |Cite
|
Sign up to set email alerts
|

Social Robots Acceptance and Marketability in Italy and Germany: A Cross-National Study Focusing on Assisted Living for Older Adults

Abstract: In the last years, social robots have become a trending topic. Indeed, robots which communicate with us and mimic human behavior patterns are fascinating. However, while there is a massive body of research on their design and acceptance in different fields of application, their market potential has been rarely investigated. As their future integration in society may have a vast disruptive potential, this work aims at shedding light on the market potential, focusing on the assistive health domain. A study with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Four studies have investigated the correlation between perceived ease of use and the acceptance of socially assistive robots among older adults (Chen & Chan, 2014; Ezer et al, 2009; Fracasso et al, 2022; Heerink et al, 2008), including 1256 participants. In a random-effects model, perceived ease of use was positively associated with the acceptance of socially assistive robots among older adults (r = .417, 95% CI = .256–.554, p < .05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four studies have investigated the correlation between perceived ease of use and the acceptance of socially assistive robots among older adults (Chen & Chan, 2014; Ezer et al, 2009; Fracasso et al, 2022; Heerink et al, 2008), including 1256 participants. In a random-effects model, perceived ease of use was positively associated with the acceptance of socially assistive robots among older adults (r = .417, 95% CI = .256–.554, p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies have investigated the correlation between perceived hedonism and the receipt of socially assistive robots in older adults (Fracasso et al, 2022; Heerink et al, 2008) and included 128 participants. In a fixed-effects model, the effect of perceived hedonism on the receipt of socially assistive robots in older adults was positively correlated (r = .391, 95% CI = .223–.535, p < .05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Important aspects to be investigated to enable the management, monitoring, and assessment of patient care in hospitals by SAR, is the trust in robotic decision support among nurses and doctors [ 25 , 26 ] and the expectation toward robots [ 27 ]. Even if several issues arouse about the actual use of robots in clinical practice (such as economic feasibility, acceptance among clinical staff, acceptance among patients) [ 28 , 29 ], the results obtained by Gombolay et al [ 30 ] sustained that the robot provided high-quality recommendations for delivery tasks, with a compliance rate of 90% respect to the clinical experts. Additionally, D’Onofrio et al [ 6 ] investigate the use of SAR in supporting the work of professionals in administering the comprehensive geriatric assessment that includes also physical and cognitive tests (e.g.…”
Section: Related Workmentioning
confidence: 99%
“…One of the applications of particular interest, both at the research and commercial level, are cognitive assistants in the shape of companion robots. These companion robots, capable of assisting older adults in their daily tasks [5], keeping them company [5], organizing their activities [6], and monitoring their medication [7], and cognitive activities [8], are being widely marketed to individuals or senior centers. Several studies have demonstrated the applicability of CA for elderly care.…”
Section: Related Workmentioning
confidence: 99%